ASSESSMENT OF GROUNDWATER QUALITY PARAMETERS OF JAEN DISTRICT, KANO STATE, NIGERIA - SULEIMAN, AHMAD ABUBAKAR; ABDULLAHI, USMAN ALIYU; SULEIMAN, AMINU; SULEIMAN, SULEIMAN ABUBAKAR; ABUBAKAR, BINTA; MUHAMMAD, TASI’U; KABIR ISAH, NI’IMATULLAH; HUSSAINI TAFIDA, ABDURRAHMAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
This study is based on physical and chemical parameters to assess groundwater quality of Jaen District, Kano state, Nigeria. Thirty groundwater samples were collected from different locations of the study area. The physical and chemical parameters such as electrical conductivity (EC), pH, total dissolved solid (TDS), carbonate (CO3), magnesium (Mg), sodium (Na), potassium (K), calcium (Ca), bicarbonate (HCO3), chloride (Cl), sulphate (SO4), fluoride (F), nitrate (NO3), and total hardness (TH) have been determined for drinking purposes. The correlation coefficients of different parameters were obtained. A linear regression equation was used to predict concentration of groundwater parameters that were found to have a higher level of significance in their correlation coefficients. Highly positive correlation coefficients are observed between EC and TDS; Mg and CO3; Ca and CO3; HCO3 and CO3; Ca and Mg; HCO3 and Mg; Cl and Na; Ca and HCO3; NO3 and Cl. The results indicate that all the regression equations obtained are significant at 1%. The use of these linear regression equations in assessing groundwater quality could serve as an alternative method of monitoring processes.